Surveillance of Human Echinococcosis in Castilla-Leon (Spain) between 2000-2012. - Amparo Lopez-Bernus; Moncef Belhassen-García; Montserrat Alonso-Sardón; Adela Carpio-Perez; Virginia Velasco-Tirado; Ángela Romero-Alegria; Antonio Muro; Miguel Cordero-Sánchez; Javier Pardo-Lledias (Public Library of Science (PLoS), 2015)
BACKGROUND:Cystic echinococcosis (CE) is an important health problem in many areas of the world including the Mediterranean region. However, the real CE epidemiological situation is not well established. In fact, it is possible that CE is a re-emerging disease due to the weakness of current control programs. METHODOLOGY:We performed a retrospective observational study of inpatients diagnosed with CE from January 2000 to December 2012 in the Western Spain Public Health-Care System. PRINCIPAL FINDINGS:During the study period, 5510 cases of CE were diagnosed and 3161 (57.4%) of the cases were males. The age mean and standard deviation were 67.8 ± 16.98 years old, respectively, and 634 patients (11.5%) were younger than 45 years old. A total of 1568 patients (28.5%) had CE as the primary diagnosis, and it was most frequently described in patients <45 years old. Futhermore, a secondary diagnosis of CE was usually found in patients >70 year old associated with other causes of comorbidity. The period incidence rate was 17 cases per 105 person-years and was significantly higher when compared to the incidence declared through the Notifiable Disease System (1.88 cases per 105 person-years; p<0.001). CONCLUSIONS:CE in western Spain is an underestimated parasitic disease. It has an active transmission, with an occurrence in pediatric cases, but has decreased in the recent years. The systematic search of Hospital Discharge Records of the National Health System Register (HDR) may be a more accurate method than other methods for the estimation of the incidence of CE in endemic areas.